The Proposed Neurotoxin β-N-Methylamino-l-Alanine (BMAA) Is Taken up through Amino-Acid Transport Systems in the Cyanobacterium Anabaena PCC 7120 - Wang, Zi-Qian (Toxins (Basel), 2020)
Produced by cyanobacteria and some plants, BMAA is considered as an important environmental factor in the occurrence of some neurodegenerative diseases. Neither the underlying mechanism of its toxicity, nor its biosynthetic or metabolic pathway in cyanobacteria is understood. Interestingly, BMAA is found to be toxic to some cyanobacteria, making it possible to dissect the mechanism of BMAA metabolism by genetic approaches using these organisms. In this study, we used the cyanobacterium Anabaena PCC 7120 to isolate BMAA-resistant mutants. Following genomic sequencing, several mutations were mapped to two genes involved in amino acids transport, suggesting that BMAA was taken up through amino acid transporters. This conclusion was supported by the protective effect of several amino acids against BMAA toxicity. Furthermore, targeted inactivation of genes encoding different amino acid transport pathways conferred various levels of resistance to BMAA. One mutant inactivating all three major amino acid transport systems could no longer take up BMAA and gained full resistance to BMAA toxicity. Therefore, BMAA is a substrate of amino acid transporters, and cyanobacteria are interesting models for genetic analysis of BMAA transport and metabolism.